Inclusion of marginalized groups in rural WATSAN in Sri Lanka - Ananda Dissanayake (2003)
This paper discusses the approach and strategies adopted by the ADB assisted Rural Water Supply Project to include marginalized communities in water supply facilities in Sri Lanka based on the appraisal carried out including a field survey in 24 heterogeneous communities.